EXAMINING THE SUSTAINABLE GROWTH OF AGRICULTURAL TOURISM IN THE STATE OF MAHARASHTRA (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Agritourism, the fusion of agriculture and tourism, has gained prominence as a unique travel experience  offering rural settings and agricultural activities to tourists. This study focuses on the sustainable growth of agritourism,  particularly in Maharashtra, India. Objectives: To investigate the scope of agri tourism and to study the potential of  agritourism in domestic market. Methodology: Research design was descriptive in nature. The study was conducted  in the cities of the state of Maharashtra: Pune, Aurangabad, Nagpur, Thane, Raigad, Pune, and Satara. 125 potential  tourist were selected for the study. The samples were selected on the basis of convenience sampling technique. Tool used  for collection of data was online questionnaire. Data was analyzed on the basis age, gender, educational qualification,  annual income & place of residents of the respondents and statistical analysis was done on percentage basis. Results:  It was found that 72% of the respondents were aware of the concept of agritourism. The interest level of the potential  tourist in various activities of agritourism varied: 22.3% of the respondents were interested in tasting local food, learning  local culture & tradition response percentage was 17.8%, for learning local cooking it was 17.5%, relaxation was 16%,  farming experiences was 13.2%, and participation in local handicraft response percentage was 10.5%. Conclusion: The study concluded that agritourism holds significant potential in India, offering additional income opportunities  for farmers and enhancing rural economies. Recommendations include the establishment of collaborative societies,  government support, and strategic partnerships to promote and sustain agritourism development in Maharashtra and  beyond.
Keywords: Agritourism; Sustainable; MTDC; Eco friendly; ATDC; Farmers Employment